Dapagliflozin improves diabetic kidney disease by inhibiting ferroptosis through β-hydroxybutyrate production - Yan Tian; Chenxia Zhou; Qun Yan; Ziyi Li; Da Chen; Bo Feng; Jun Song (Renal Failure)
Background Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease. Sodium-glucose cotransporter protein 2 inhibitors (SGLT2i) are antihyperglycemic agents that provide additional renal-protective effects in patients with DKD, independent of their glucose-lowering effects. However, the underlying mechanism remains unclear. This study hypothesized that SGLT2i could alleviate diabetic kidney injury by inhibiting ferroptosis and explored its potential mechanisms.Methods C57BL/6J mice were randomly divided into the control, DKD, DKD+dapagliflozin, and DKD+insulin treatment groups. Blood glucose levels and body weight were monitored. Renal function, tissue pathology, mitochondrial morphology and function, and lipid peroxidation biomarkers (lipid peroxidation [LPO], malondialdehyde [MDA], glutathione peroxidase 4 [GPX4], glutathione [GSH], and cystine transporter solute carrier family 7 member 11 [SLC7A11]) were evaluated. Human proximal tubule cells (HK2 cells) were exposed to high glucose alone or in combination with dapagliflozin. The mitochondrial membrane potential (MMP), adenosine triphosphate (ATP) level, NAD+/NADH ratio (oxidized/reduced ratio of nicotinamide adenine dinucleotide), and lipid peroxidation were measured. In addition, the role of the β-hydroxybutyrate- Calcium/Calmodulin Dependent Protein Kinase Kinase 2 (BHB-CaMKK2) axis in mediating dapagliflozin regulating ferroptosis was examined.Results Dapagliflozin significantly ameliorated kidney injury in mice with DKD. Typical changes in ferroptosis, including lipid peroxidation and impaired antioxidant capacity, increased in mice with DKD and HG-treated HK-2 cells. Dapagliflozin significantly improves ferroptosis-related lipid peroxidation and mitochondrial dysfunction. Furthermore, dapagliflozin suppressed the expression of CaMKK2, a key ferroptosis regulator. Specific CaMKK2 inhibitors alleviated mitochondrial damage and ferroptosis, whereas a CaMKK2 agonist counteracted the protective effects of dapagliflozin against mitochondrial, antioxidant, and anti-ferroptosis effects. In addition, dapagliflozin increased BHB production, which mediates its nephroprotective effects.Conclusion Dapagliflozin improves DKD by inhibiting ferroptosis, promoting BHB production, and regulating CaMKK2.